A Synopsis of Factors of Injuries in Road Traffic Accidents in Lagos, Nigeria - Atubi, Augustus .O. (Mediterranean Journal of Social Sciences, 2013)
The purpose of this study is to examine the factors of injuries from road traffic accidents in Lagos State, Nigeria and to suggestpreventive and corrective safety measures towards reducing the traffic accidents in the study area. The reported number ofinjuries from road traffic accidents in the 20 Local Government Areas of Lagos State from 1970-2001 were compared using theAnalysis of Variance (ANOVA). The result showed that for the two factors, Local Government Areas and years, the f-calculatedof 21.34 and 9.77 respectively were higher than the f-tabular of 1.57 and 1.46 respectively at 0.05 level of significance. It thenimplies that the means for each of the factors, reported number of injuries across the 20 Local Government Areas in LagosState and across different years, 1970-2001, were significantly different. The result of the multiple regression analysis was0.61. This implies that the proportion of variation in the dependent variables (i.e. length of roads, presence of road safety corpsand population) was 61%. The F-ratio of 14.34 was higher than table value of 2.92 at 0.05 level of confidence. This shows thatat least one of the independent variable had significant influence on the dependent variable. Based on the findings,recommendations were proffered.